Problematized Experimental Activity: A methodology based on author narrative - Gonçalves, Fernanda Tarouco (2021)
This study aims to describe and analyze the Problematized Experimental Activity – AEP principles, considering that experimental teaching is a tendency to motivate students to learn Science, especially when it has a more investigative character. For that, AEP´s author was interviewed, and his answers were submitted to theoretical reading and saturation, emerging a Grounded Theory in Data. The findings of this work lead to the consideration of AEP as an efficient and attractive methodology to promote autonomy and generate meanings in the learning process.